2011
DOI: 10.11613/bm.2011.021
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 13 expression in the primary breast cancer tumor tissue

Abstract: 131 Ab stra ctIn tro duc tion: The aim of this stu dy was to in ves ti ga te the pre sen ce and the expres sion le ve ls of the in ter leu kin 13 (IL-13) in the pri ma ry brea st cancer tu mour tis sue in re la tion to the un chan ged brea st tis sue in the sa me pa tien ts and to the brea st tis sue in the pa tien ts wi th be ni gn brea st di sea se, and to in ves ti ga te the cor re la tion be tween the IL-13 expres sion le ve ls and the pat ho his to lo gi cal fac to rs, and be tween IL-13 expres sion and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 4 publications
1
25
1
Order By: Relevance
“…It has dual effect on cancer; ex part it has anti-tumor activities that are mediated by increasing of NK cell activity and induction of apoptosis in tumor cells (Srabovic et al, 2011). Besides, IL-18 has also been found to promote tumor progression (Park et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has dual effect on cancer; ex part it has anti-tumor activities that are mediated by increasing of NK cell activity and induction of apoptosis in tumor cells (Srabovic et al, 2011). Besides, IL-18 has also been found to promote tumor progression (Park et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of IL-18 have been detected in various cancers. Besides, elevated IL-18 expression has been associated with tumor growth and metastasis in breast cancer (Gunel et al, 2002;Srabovic et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…IL13 is upregulated in primary breast cancer tissue [72] and in the peripheral blood of patients with pancreatic, esophageal, and gastric cancer [73]. While studies focusing on the implications of IL13 signaling in epithelial cancer cells are limited, it is known to have both pro-tumorigenic and pro-metastatic roles as we have previously reviewed [2].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…IL13 can signal through type II IL4R (IL4Rα and IL13Rα1) or through IL13Rα2, once believed to serve only as a decoy receptor. Elevated levels of IL13 were detected in primary breast cancer tumor tissue (24) and in the peripheral blood of 131 other cancer patients (pancreatic, esophageal and gastric) when compared to healthy controls (25). Recent studies by Formentini, et al and Barderas, et al suggested possible roles for IL13 and its receptors IL13Rα1 and IL13Rα2 in colorectal cancer (11, 26).…”
Section: Il13 and Its Receptorsmentioning
confidence: 99%